2022
DOI: 10.3390/ijms23042078
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Neutralizing Activity of Antibodies Targeting Open or Closed SARS-CoV-2 Spike Protein Conformations

Abstract: SARS-CoV-2 infection elicits a polyclonal neutralizing antibody (nAb) response that primarily targets the spike protein, but it is still unclear which nAbs are immunodominant and what distinguishes them from subdominant nAbs. This information would however be crucial to predict the evolutionary trajectory of the virus and design future vaccines. To shed light on this issue, we gathered 83 structures of nAbs in complex with spike protein domains. We analyzed in silico the ability of these nAbs to bind the full … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…• Antigens can undergo conformational changes where some regions get masked and become unavailable for antibody binding. The spike protein trimer of SARS-CoV-2 is an example of this: it occurs in open and closed conformations characterized by differences in solvent accessibility and epitopes [57].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…• Antigens can undergo conformational changes where some regions get masked and become unavailable for antibody binding. The spike protein trimer of SARS-CoV-2 is an example of this: it occurs in open and closed conformations characterized by differences in solvent accessibility and epitopes [57].…”
Section: Discussionmentioning
confidence: 99%
“…In order to evaluate the ability of the benchmarked methods to predict the known epitopes in the spike protein, we gathered 83 spike protein-antibody complexes resolved by X-ray crystallography or cryo-electron microscopy and deposited in the PDB [5] (see [57,58] for the list of PDB ids). We extracted 83 epitopes from these complexes; 75 of them are localized on the RBD of the spike protein, while the remaining eight target its N-terminal domain (NTD).…”
Section: Sars-cov-2 Case Studymentioning
confidence: 99%
“…remains unchanged in terms of amino acid sequence, in contrast to, for example, peptide 32 ( , (accessed on 28 November 2022)). Notably, monoclonal antibodies with virus-neutralizing ability targeting the N-terminal domain (NTD) region of which peptide 12 is a part thereof have been described [ 31 ], and it was reported that also other vaccines can induce an antibody response directed against this region [ 18 , 19 , 20 , 32 ], indicating that the region defined by peptide 12 may be important for inducing neutralizing antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Thus MIAs can only measure whether antibodies can prevent the interaction of RBD and ACE2. In this context, it must be mentioned that epitopes located outside RBD in the S protein may also play a role in virus-neutralization [ 45 , 46 , 47 , 48 , 49 , 53 , 126 , 127 ]. It is thus possible that certain subjects lacking antibodies blocking the RBD–ACE2 interaction may still contain NAbs.…”
Section: Molecular Interaction Assays Miasmentioning
confidence: 99%